Some Historical Aspects of the Establishment and Development of the ”Vor V Zakone” E Bis Institute - Tsereteli, Ioseb (Journal of Legal Studies, 2022)
Organized crime is the most dangerous type of criminal activity because organized crime associations run the criminal environment and commit various types of serious criminal acts. The fight against organized crime is, therefore, a priority for individual countries as well as for the world community as a whole. To combat this phenomenon, the United Nations adopted the Convention against Transnational Organized Crime on November 15, 2000, which has been ratified by many countries around the world. In addition, one of the types of organized crime is the so-called "thieves in law" institute, which originated in the former Soviet Union and is known around the world as the Russian mafia, namely the Russian term "Vory v Zakone", which means "thieves in law". means. Today, their criminal activities are widespread in many countries. We believe that in order to fight against this criminal association, it is necessary to study the history of its emergence and development. That is why our goal is the so-called. A study of the history of the institute of "thieves in law" and some peculiarities.